Evil and Death Conceptions of the Human in Biblical, Early Jewish, Greco-Roman and Egyptian Literature - Ego, Beate 1958-; Mittmann-Richert, Ulrike 1961- (Berlin Bosten De Gruyter, 2015)
Jewish anthropological beliefs during the Hellenistic-Roman period are an important but previously neglected area of biblical exegesis and Jewish studies. In an effort to address this deficiency, this volume brings together 20 essays related to the subject of sin and death, with special emphasis on integrating material from neighboring cultures. Thus, the volume provides an exemplary foundation for further research on ancient Jewish anthropology.
Frontmatter -- Foreword -- Contents -- Part I: Old Testament and Early Jewish Literature -- Das Böse und der Tod in der Paradieserzählung – Biblische und auslegungsgeschichtliche Aspekte -- An des Todes Pforten weise werden – Überlegungen im Anschluss an Psalm 107 -- Curse God and Die — Job’s Wife and the Struggle for Job’s Transformation -- Evil and Death in the Book of Qohelet -- Different Approaches to Evil and Death in the Ethics of the Non-Canonical Jewish Writings -- Das Bild des Menschen im Wandel – Die Rezeption von Genesis 1–3 in Sapientia Salomonis 1 und 2 -- Human Experience and the Problem of Theodicy in 4 Maccabees -- The Post-mortem Divisions of the Dead in 1 Enoch 22:1–13 -- „Dem Tode verfallen war ich wegen meiner Sünden“ (11QPsa XIX,1–18) -- Part II: New Testament -- The Child, Death and the Human in Mark’s Gospel -- Reversal of Fate after Death? -- Death and Cultus as Constitutive of the Human in the Epistle to the Hebrews -- Part III: Greco-Roman and Egyptian Literature -- Trauer und Tod in der 2. Sophistik am Beispiel des Lukian von Samosata -- Privatdeifikationen in der römischen Kaiserzeit – Tod, Trauer und Memoria -- Tod auf der Latrine— Zum Ende von Caracalla und Elagabal -- Der Religionsstifter Numa im Gespräch mit Jupiter -- Narrating Meleager’s Deeds and Death in Words and Images -- „Sage nicht: ‚Der Frevler gegen Gott lebt heute‘; auf das Ende sollst du achten!“ -- Index of Names and Subjects (German) -- Index of Names and Subjects (English) -- Bible Citation Index
Reproduktion
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Death -- Biblical teaching; Egyptian literature -- History and criticism; Good and evil -- Biblical teaching; Greek literature, Hellenistic -- History and criticism; Egyptian literature; Good and evil; Greek literature, Hellenistic; Ägyptisch; Altertum; Das Böse; Frühjudentum; Griechisch; Hellenistisch-jüdische Literatur; Latein; Literatur; Philosophie; Sünde; Tod; Übel; Death; RELIGION / Antiquities & Archaeology; RELIGION / Christian Theology / Eschatology; RELIGION / Biblical Criticism & Interpretation / New Testament; Religion / Judaism / History; RELIGION / Biblical Criticism & Interpretation / Old Testament; Religion / History; RELIGION / Judaism / Sacred Writings; Sin; Death; Anthropology; hamartology